A postcolonial perspective on regional literature in Australia - Henningsgaard, Per (Cambria Press, 2010)
Within Australia, the concentration of the “field of cultural production” in Sydney and Melbourne results in the perception that the local and specific of these places constitutes the “universal.” Any attention paid to the local and specific in the cultural products of other Australian locations, such as Western Australia, therefore constitutes the “regional.” In an international or global context, however, Australia constitutes the “regional” rather than the “universal,” since the relatively greater concentrations of instruments of cultural production in places such as London and New York City indirectly confers upon them the latter title. Clearly, there is a parallel between the dynamic that governs Australia’s negotiations with the international literary community, and the dynamic that governs the negotiations of a more conventionally conceived region (such as Western Australia) with its national literary culture. Furthermore, there are parallels between this dynamic and the dynamic responsible for producing postcolonial literature, a literary movement that “asserted [itself] by foregrounding the tension with the colonial power, and emphasising ... differences from the assumptions of the imperial centre.” This chapter hopes that by emphasizing the postcolonial nature of Australian literature and analyzing Australian texts from a postcolonial theoretical perspective, it might diversify our understanding of Australian literature by supporting the introduction of a regional perspective. (Supplied by author).